Malik, R., & Naveed, A. (2015). Financing Education in Pakistan: The Impact of Public Expenditure and Aid on Educational Outcomes. RECOUP WP, no. 42. - Qutoshi, Sadruddin Bahadur (Dhaulagiri Journal of Sociology and Anthropology, 2017)
No abstract availableDhaulagiri Journal of Sociology and Anthropology Vol.11, 2017; 190-196